Flavokawain derivative FLS induced G2/M arrest and apoptosis on breast cancer MCF-7 cell line - Ali, N.M.; Akhtar, M.N.; Ky, H.; Lim, K.L.; Abu, N.; Zareen, S.; Ho, W.Y.; Alan-Ong, H.K.; Tan, S.W.; Alitheen, N.B.; Ismail, J.B.; Yeap, S.K.; et al. (Dove Medical Press, 2016)
Known as naturally occurring biologically active compounds, flavokawain A and B are the leading chalcones that possess anticancer properties. Another flavokawain derivative, (E)-1-(2′-Hydroxy-4′,6′-dimethoxyphenyl)-3-(4-methylthio)phenyl)prop-2-ene-1-one (FLS) was characterized with 1H-nuclear magnetic resonance, electron-impact mas spectrometry, infrared spectroscopy, and ultraviolet (1H NMR, EI-MS, IR, and UV) spectroscopic techniques. FLS cytotoxic efficacy against human cancer cells (MCF-7, MDA-MB-231, and MCF-10A) resulted in the reduction of IC50 values in a time- and dose-dependent mode with high specificity on MCF-7 (IC50 of 36 μM at 48 hours) against normal breast cell MCF-10A (no IC50 detected up to 180 μM at 72 hours). Light, scanning electron, and fluorescent microscopic analysis of MCF-7 cells treated with 36 μM of FLS displayed cell shrinkage, apoptotic body, and DNA fragmentation. Additionally, induction of G2/M cell arrest within 24 hours and apoptosis at subsequent time points was discovered via flow cytometry analysis. The roles of PLK-1, Wee-1, and phosphorylation of CDC-2 in G2/M arrest and proapoptotic factors (Bax, caspase 9, and p53) in promotion of apoptosis of FLS against MCF-7 cells were discovered using fluorometric, quantitative real-time polymerase chain reaction, and Western blot analysis. Interestingly, the presence of SCH3 (thiomethyl group) on ring B structure contributed to the selective cytotoxicity against MCF-7 cells compared to other chalcones, flavokawain A and B. Overall, our data suggest potential therapeutic value for flavokawain derivative FLS to be further developed as a new anticancer drug.